Student response of Medan State University to independent campus discussion - Wahyuni, Indah; Anshori, Akhyar (COMMICAST, 2021)
Some time ago, Minister of Education and Culture (Mendikbud) Nadiem Makarim launched a program called "Merdeka Learning" aimed at Universities / Colleges which is also known as the Independent Campus. The discourse conveyed by the Minister of Education and Culture regarding the Merdeka Campus has four policies in the scope of higher education, namely (1) Opening of new study programs, in which this program provides autonomy for State (PTN) and Private Universities (PTS) to open or establish new study programs, (2) Higher education accreditation system, (3) Freedom for PTN Public Service Agency (BLU) and Work Unit (Satker) to become PTN Legal Entity (PTN BH), (4) Right for students to take courses outside the study program and changing the definition of the Semester Credit System (SKS). The purpose of this study was to determine how the Medan State University Student Response to the Discourse of the Merdeka Campus. The data collection technique used in this study used several methods including literature study, observation, interviews, and documentation. This data analysis technique uses a qualitative descriptive method which is used to describe a situation that is currently running at the time the research is carried out and examines the causes of a particular symptom, then analyzed by conducting a conceptual examination of a statement so that the clarity of the meaning contained in the statement can be obtained. the. Where all the speakers know the discourse on an independent campus that has been conveyed by the Minister of Education and Culture some time ago, but from the results of the interviews conducted in more depth, five people only approved and three people did not approve of the independent campus.Â